Network neutrality, access to content and online advertising - Anna D'Annunzio; Antonio Russo (ETH Zurich, KOF Swiss Economic Institute, 2013)
We investigate the implications of Network Neutrality regulation for Internet fragmentation. We model a two-sided market, where Content Providers (CPs) and consumers interact through Internet Service Providers (ISPs) and CPs sell consumers' attention to advertisers. Under Network Neutrality, CPs can have their traffic delivered to consumers by ISPs for free, while in the Unregulated Regime they have to pay a (non-discriminatory) termination fee. In our model multiple impressions of an ad on a consumer are partially wasteful. Thus, equilibrium ad rates decrease when the audiences of CPs overlap. We show that universal distribution of content is always an equilibrium when Network Neutrality regulation is in place. In contrast, when competition among CPs strongly reduces their profits, in the Unregulated Regime ISPs can use termination fees to induce fragmentation and extract CPs' extra profits. This occurs when repeated impressions of an ad rapidly lose value and consumers care for content availability to a relatively small extent. Our results suggest that the Unregulated Regime is never superior to Network Neutrality from a consumer surplus and social welfare point of view.
Keywords: L1; D43; L13; L51; 330; Network Neutrality; two-sided markets; Internet; advertising; fragmentation; Internet; Netzregulierung; Internetbasierter Dienst; Netzwerkökonomik; Theorie